Metal fuels for renewable energy storage and circular economy - Alberto Boretti; Stefania Castelletto (Next Energy, 2025)
The growing demand for sustainable, large-scale energy storage has sparked significant interest in metal fuels, such as aluminum, iron, magnesium, and zirconium, as high-energy-density, carbon-free alternatives to fossil fuels. This narrative review examines the potential of metal fuels for renewable energy storage within a circular economy framework. It highlights the oxidation of metal fuels in air, steam, and carbon dioxide, with air and steam oxidation proving particularly effective for heat generation and facilitating hydrogen production. The review further explores electricity generation through thermal cycles and evaluates methods for recycling metal oxides into reusable fuels via electrolysis, noting the high-energy requirements and associated carbon emissions in established processes. While the technology readiness level (TRL) for metal fuel combustion for power generation remains relatively low (estimated TRL 3–4), processes for recycling metal oxides, such as the Hall-Héroult process for aluminum, exhibit higher TRLs (TRL 9). Several of these metals, such as magnesium and potentially zirconium (depending on the region and specific list criteria), are considered critical raw materials, adding complexity to their large-scale use as energy carriers. Despite offering advantages in storage compared to hydrogen, metal fuels face limitations due to the restricted availability of metal oxides compared to the abundance of water for hydrogen storage. As such, metal-based energy storage should not be seen as competing with hydrogen-based solutions but as a complementary approach. By aligning with circular economy principles, metal fuels can address specific energy storage needs while supporting the recycling of metal oxides.